The chemical and oxidation characteristics of semi-dry flue gas desulfurization ash from a steel factory - Liu, Ren-ping (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2010)
Some samples of semi-dry flue gas desulfurization (FGD) ash were taken from sinter gas of a steel factory. Scanning electron microscope (SEM) and X-ray diffraction (XRD) analyses were employed to identify the samples in order to investigate their physical and chemical characteristics. The results show that semi-dry FGD ash from a steel factory is stable under atmospheric conditions. It has irregular shape, a smooth surface and loose construction. The size of FGD ash particles is around 0.5-25 µm, the average size is about 5 µm and the median diameter is 4.18 µm. Semi-dry FGD ash from a steel factory consists of CaSO₃, CaSO₄, CaCO₃, some amorphous vitreous material and unburned carbon. An experimental method was found to study the oxidation characteristics of ash. A prediction model of the oxidation efficiency was obtained based on response surface methodology. The results show that not only the temperature, but also gas:solid ratio, play an important role in influencing the oxidation efficiency. The interactions of the gas:solid ratio with temperature play an essential role. An improved response surface model was obtained which can be helpful to describe the degree of oxidation efficiency of semi-dry FGD ash